THE DICTIONARY OF MODERN PROVERBS: FOURTH SUPPLEMENT - Doyle, Charles Clay; Mieder, Wolfgang (Proverbium - Yearbook, 2022)
This is the fourth supplement to The Dictionary of Modern Proverbs (New Haven, Connecticut: Yale University Press, 2012), edited by Charles Clay Doyle, Wolfgang Mieder, and Fred R. Shapiro. It registers 43 additional modern Anglo-American proverbs with historical dates and contextualized references.